2022
DOI: 10.1111/adb.13171
|View full text |Cite
|
Sign up to set email alerts
|

2‐Fluorodeschloroketamine has similar abuse potential as ketamine

Abstract: 2‐Fluorodeschloroketamine (2‐FDCK) as a substitute for ketamine has emerged among drug abusers in recent years. However, 2‐FDCK has not been controlled or regulated in many countries, which may be partly related to the lack of evidence on its abuse potential. In this study, we evaluated the abuse potential of 2‐FDCK via the tests of the conditioned place preference (CPP), locomotor sensitization, drug self‐administration and drug discrimination using ketamine as a reference. 2‐FDCK induced significant CPP at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…The main findings of the present study are that both the α parameter and the EV of effectiveness between 2F-DCK and ketamine are similar, and the reinstatement of 2F-DCKand ketamine-seeking behaviors after extinction is also similar. These data, along with the data from previous studies, suggest that 2F-DCK and ketamine have abuse potential and can cause cravings after extinction (Huang et al, 2015;Li et al, 2022]. The value of the α parameter is inversely proportional to the intensity of reinstatement of 2F-DCK-and ketamineseeking behaviors, which could predict cravings for 2F-DCK and ketamine after withdrawal from self-administration.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…The main findings of the present study are that both the α parameter and the EV of effectiveness between 2F-DCK and ketamine are similar, and the reinstatement of 2F-DCKand ketamine-seeking behaviors after extinction is also similar. These data, along with the data from previous studies, suggest that 2F-DCK and ketamine have abuse potential and can cause cravings after extinction (Huang et al, 2015;Li et al, 2022]. The value of the α parameter is inversely proportional to the intensity of reinstatement of 2F-DCK-and ketamineseeking behaviors, which could predict cravings for 2F-DCK and ketamine after withdrawal from self-administration.…”
Section: Discussionsupporting
confidence: 62%
“…Our previous studies have shown that 2F-DCK produces self-administration, conditions place preference, and generalizes discriminative stimuli effects similar to ketamine (Li et al, 2022). Behavioral economics provides a framework for quantifying 2F-DCK and ketamine abuse potential, while also offering an approach complementary to the self-administration and dose-response curve used previously to characterize the abuse-related effects of 2F-DCK and ketamine (Li et al, 2022). Thus, the α parameter and EV values of 2F-DCK and ketamine were very close, indicating that both have similar reinforcing effectiveness.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations